Estudo da biologia reprodutiva de Nycticorax nycticorax no Parque Estadual Fontes do Ipiranga, São Paulo - Costa, Yanna Dias (2015)
Data on the reproductive biology of birds are essential to test hypotheses regarding the evolution of different aspects of the life history of these animals. However, basic information on the reproductive behavior of most South American bird species are poorly known. Moreover, particularly for birds with wide geographic distribution, life history may vary according to the different environmental conditions. Thus, the study of reproductive behavior in different populations of the same species, allow the identification of patterns of variation to make inferences about the ecological and evolutionary mechanisms responsible for the diversification and facilitates the development of conservation strategies. The Black Crowned Night Heron, Nycticorax nycticorax (Ardeidae) is a cosmopolitan species very common in Brazil, which breeds in large colonies. Although data on the reproductive biology of this species are available for Europe and North America, is little studied in Brazil. Thus, the objective of this proposal is to describe the reproductive cycle of N. nycticorax in two colonies in the Parque Estadual Fontes do Ipiranga, São Paulo, southeastern Brazil. The breeding season extended from July of 2013 to January 2014, however the field work was performed from September to January, with peak activity in September. The nests were built average 3,55 ± 2,58 m high and 2,36 ± 1,62 m alway from the main trunk. A total of 38 nests were found, but just 29 were monitored. The clutch size was 2.41 ± 0.68 (1 - 3) n = 29, and the incubation period was 23,26±1,26. The nestlings began to leave the nest with an average of 17.4 ± 3.6 days of life, what we call the stay 1, and left the nest definitely with 25,71 ± 7,16 days, which we call the residence 2. From 70 eggs, 57.14 % hatched and 25 chicks survived and left the nest. The survival rate was 31% from laying to the left of the nest, Mayfield. We compared with other tropical populations and the Northern Hemisphere, we recorded a strong tendency in latitudinal gradients of larger clutch size at high latitudes, but reproductive success does not seem to be associated with it, should be more associated with habitat conditions and availability of resources than with the latitudes. Incubation seem to support the premise to be higher in tropical regions, but few incubation data and nestling data are available for comparison.